Risking the “Transculturation” in Tiempo al tiempo by Isaac Goldember (ALPHA. Journal of Arts, Literature and Philosophy, 1998)
This essay is an analysis of the concept of “Transculturation” in the contemporary Peruvian context. From the fragmented subjectivity of the novel’s protagonist, a Jewish Mestizo from Peru, this concept can be redefined. Instead of the linear process proposed by Fernando Ortiz and reprocesed by Angel Roma, whose theories simplify the broken and conflictive realities of Peruvian identity, transculturation presents itself in Tiempo al tiempo by Isaac Goldemberg as a convergence of time and spaces with borders that are often fragmented and eroded.